2009
DOI: 10.1016/j.ejso.2009.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Combined liver surgery and RFA for patients with gastroenteropancreatic endocrine tumors presenting with more than 15 metastases to the liver

Abstract: Please cite this article as: Elias D., Goéré D., Leroux G., Dromain C., Leboulleux S., de Baere T., Ducreux M., Baudin E. Combined liver surgery and RFA for patients with gastroenteropancreatic endocrine tumors presenting with more than 15 metastases to the liver., European Journal of Surgical Oncology (2009Oncology ( ), doi: 10.1016Oncology ( /j.ejso.2009 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 23 publications
3
55
0
8
Order By: Relevance
“…Based on this concept, even more PSHs for CRLMs were performed in recent years. [24][25][26] This change of 9 who demonstrated that, in case of single CRLM of 3 cm, the parenchymal-sparing technique improved survival in case of liver recurrence, allowing for salvage re-hepatectomy as compared to a NON-PSH approach. To our knowledge, there was no report in the literature establishing a comparison between NON-PSH and PSH for multiple bilobar resections for more than 3 lesions which analyzed shortterm and long-term results.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this concept, even more PSHs for CRLMs were performed in recent years. [24][25][26] This change of 9 who demonstrated that, in case of single CRLM of 3 cm, the parenchymal-sparing technique improved survival in case of liver recurrence, allowing for salvage re-hepatectomy as compared to a NON-PSH approach. To our knowledge, there was no report in the literature establishing a comparison between NON-PSH and PSH for multiple bilobar resections for more than 3 lesions which analyzed shortterm and long-term results.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical options include resection or rarely transplantation, but the majority of patients do not have resectable or "transplantable" disease at presentation, and surgery carries a high recurrence rate (13)(14)(15)(16). Somatostatin analogues are the most effective pharmacologic therapy for symptom control, and traditional chemotherapy has limited efficacy (17,18).…”
mentioning
confidence: 99%
“…However, liver surgery is frequently impossible due to the extent of the disease. Various surgical approaches have been proposed to these patients, such as a two-step surgical procedure or a combination of surgery and radiofrequency ablation [5,6,7,8]. Even with the development of these techniques, the resection of more than 10 or 20 bilateral lesions is usually considered as unfeasible.…”
Section: Introductionmentioning
confidence: 99%